Effect of electrical injection-induced stress on interband transitions in high Al content AlGaN MQWs. Issue 87 (5th December 2017) - Zheng, Jinjian; Li, Jinchai; Zhong, Zhibai; Lin, Wei; Chen, Li; Li, Kongyi; Wang, Xinghe; Chou, Chilun; Li, Shuiqing; Kang, Junyong
Abstract : The light extraction from AlGaN deep ultraviolet light-emitting diodes (UV LEDs) is known to be limited by the fundamental valence band crossover issue. Abstract : The light extraction from AlGaN deep ultraviolet light-emitting diodes (UV LEDs) is known to be limited by the fundamental valence band crossover issue. To study the effect of electrical injection on the complex structure of the valence bands, stress variations were characterized by the Raman shift of AlGaN deep UV LEDs under electrical injection. Results show that tensile stress builds up as the current increases. The first-principles simulations reveal that, as the tensile strain increases, the crystal-splitting hole band becomes more dominant at the top of valence bands and exhibits stronger dispersion along the Γ – A direction, leading to stronger TM polarized emission and a decrease of the total spontaneous emission rate. Furthermore, a promising way of controlling AlGaN MQWs under strain-free or compressive strain status is proposed to improve the transverse electric polarized emission and quantum efficiency in deep UV LEDs.